40Ar–39Ar ages and isotope geochemistry of Cretaceous basalts in northern Madagascar: Refining eruption ages, extent of crustal contamination and parental magmas in a flood basalt province - Cucciniello, C.; Melluso, L.; Jourdan, Fred; Mahoney, J.; Meisel, T.; Morra, V. (Cambridge University Press, 2013)
The Madagascar Cretaceous igneous province exposed in the Mahajanga basin is represented by basalt and basaltic andesite lavas. New 40Ar–39Ar plateau ages (92.3 ± 2.0 Ma and 91.5 ± 1.3 Ma) indicate that the magmatism in the Mahajanga basin started about 92 Ma ago. Four geochemically distinct magma types (Groups A–D) are present. Group A and C rocks have low to moderate TiO2 (1.2–2.6 wt%), Nb (3–9 μg g−1) and Zr (82–200 μg g−1), and show large variations in ɛNdi (+0.1 to −10.8), 206Pb/204Pb (15.28 to 16.33) and γOs (+11.4 to +7378). The large isotopic variations, particularly in Os, Nd and Pb isotopic compositions, are likely due to crustal contamination. The low Pb isotope ratios observed in the Group A and C rocks suggest involvement of continental crust with low μ (238U/204Pb). Group B and D rocks have moderate to high TiO2 (2.2–4.9 wt%), Nb (8–24 μg g−1) and Zr (120–327 μg g−1). Age-corrected isotopes of Group B and D lavas show a small range in ɛNdi (+1.0 to +4.0) and a wide range in γOs (+128 to +1182). Values of 207Pb/204Pb are within the range for Groups A and C, but the Group D 206Pb/204Pb (16.52–17.08) and 208Pb/204Pb (37.51–38.01) values are higher, indicating a different crustal contaminant. Pb isotopic values of the Group B rocks seem to reflect the isotopic features of their mantle source. The magma groups of Mahajanga display a wide range of trace element and isotopic compositions that cannot be explained only by open-system crystallization processes but, rather, by distinct mantle sources.